Risk assesstment of noise exposure in wooden furniture manufacturing industry - Chan, Chia Jing (2015)
A cross-sectional study was conducted to investigate the noise exposure and noise induced hearing loss (NIHL) symptoms among workers in wooden furniture manufacturing industry. Environmental noise monitoring was carried out by using sound level meter (SLM) to assess the noise level in different workstations. Personal noise monitoring was conducted by using portable dosimeter to monitor personal noise exposed among workers. Questionnaire was developed to obtain demographic information, job profile and health history of respondents. Meanwhile, walk-through survey and interview was conducted to identify the sources of noise and other related factors. The area noise level measurements showed that the molding operation recorded the highest noise level in the industry compared to other operations. The respondents who work with machine were randomly chosen from the selected block and they were divided into high and low exposure group. Personal noise measurement shows that 60% of respondents exposed to low noise level (85-90 dBA) whereas 40% of respondents exposed to high noise level (> 90 dBA). There was a significant different (t = -11.289, p = 0.001) of personal noise level between low and high exposed group. Besides that, NIHL symptoms complaints among the exposed worker shows that prevalence of tinnitus among the highly exposed group was significantly higher than the low exposed group (x2 = 11.667,p = 0.001). The factors such as personal noise level (p = 0.026) and employment period (p = 0.010) shows significant relationship with ear pain whereas only personal noise level (p = 0.001) shows significant relationship with tinnitus. This might due to bad work practices among workers who did not wearing appropriate PPE during performing their work as observed throughout the study period. Hence, the use of noise protection gadget among workers and other control measure within the wooden furniture industry is strongly recommended to ensure the workers' safety and health.